2007
DOI: 10.1093/nar/gkm202
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of a very long oligoribonucleotide with 2-cyanoethoxymethyl (CEM) as the 2′-O-protecting group: structural identification and biological activity of a synthetic 110mer precursor-microRNA candidate

Abstract: A long RNA oligomer, a 110mer with the sequence of a precursor-microRNA candidate, has been chemically synthesized in a single synthesizer run by means of standard automated phosphoramidite chemistry. The synthetic method involved the use of 2-cyanoethoxymethyl (CEM), a 2′-hydroxyl protecting group recently developed in our laboratory. We improved the methodology, introducing better coupling and capping conditions. The overall isolated yield of highly pure 110mer was 5.5%. Such a yield on a 1-μmol scale corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 34 publications
1
71
0
3
Order By: Relevance
“…Given these limitations, we turned to a chemical synthesis of pre-miRNAs (syn-premiRNA). The length of human premiRNAs (50-90 nt) is challenging for routine laboratory synthesis (Shiba et al 2007). Consequently, reports of the use of syn-pre-miRNAs as miRNA mimics are rare (see, e.g., Macrae et al 2008;Koscianska et al 2011;Starega-Roslan et al 2011) (see Siolas et al 2005 for a synthesis of shRNAs).…”
Section: Tgf-β1 Rnai Induces Mir-34a-5p and Mir-34a-3pmentioning
confidence: 99%
“…Given these limitations, we turned to a chemical synthesis of pre-miRNAs (syn-premiRNA). The length of human premiRNAs (50-90 nt) is challenging for routine laboratory synthesis (Shiba et al 2007). Consequently, reports of the use of syn-pre-miRNAs as miRNA mimics are rare (see, e.g., Macrae et al 2008;Koscianska et al 2011;Starega-Roslan et al 2011) (see Siolas et al 2005 for a synthesis of shRNAs).…”
Section: Tgf-β1 Rnai Induces Mir-34a-5p and Mir-34a-3pmentioning
confidence: 99%
“…9B). We found that substitution of acetic anhydride with phenoxyacetic anhydride (59) eliminates this artifact as shown in Fig. 9C.…”
Section: A Potential Side Reaction During Oligonucleotide Synthesis Imentioning
confidence: 62%
“…The phosphoramidite method is currently the most efficient method for the synthesis of oligonucleotides, and can produce long oligomers using an automatic synthesizer (62,63). However, the application of this method to the synthesis of glycosyl phosphate derivatives has not been well explored (64)(65)(66)(67)(68)(69).…”
Section: F Synthesis Of Glycosyl Phosphate Derivatives Using the Phomentioning
confidence: 99%